H pylori infection is associated with downregulation of E-cadherin, a molecule involved in epithelial cell adhesion and proliferation control - KELLEHER, DERMOT P (British Medical Association, 1998)
Extracellular matrix proteins and proteins involved in epithelial adhesion are essential for maintenance of tissue structure. Helicobacter pylori is the major aetiological agent in peptic ulcer disease and has been shown to increase gastric cancer risk up to ninefold. In this study, changes induced by H pylori on the expression of extracellular matrix proteins (collagen IV, fibronectin, and laminin) as well as two essential proteins for cell-basement and cell-cell adhesion (alpha 6-integrin and E-cadherin) were assessed. Immunohistochemistry was performed in antral biopsy sections obtained from infected and non-infected patients, and light microscopy was used to determine the distribution and intensity of specific staining. The results showed that the infection was significantly associated with downregulation of E-cadherin, an essential protein for maintenance of solid tissues and differentiation, but did not induce changes in the expression of alpha 6-integrin or the extracellular matrix proteins.
PUBLISHED
Keywords: Clinical Medicine